Resolution of Vitamin D Insufficiency in Osteopenic Patients Results in Rapid Recovery of Bone Mineral Density - Adams, John S; Kantorovich, Vitaly; Wu, Cindy; Javanbakht, Marjan; Hollis, Bruce W (The journal of clinical endocrinology and metabolism, 1999)
Vitamin D insufficiency is characterized biochemically by the presence of secondary hyperparathyroidism, which can contribute to bone loss in osteopenic patients. Over a 2-yr period of evaluation of 118 consecutive, free living patients with osteopenia or osteoporosis, we identified 18 subjects with depressed serum 25-hydroxyvitamin D (25OHD;≤ 14 ng/mL). Twelve of these subjects harbored a low 25OHD level and consented to undergo replacement with 50,000 IU vitamin D2 twice weekly for 5 weeks. Five hundred thousand units of oral vitamin D2 resulted in significant increases in 25OHD (+24.3± 16.9 ng/mL; P < 0.001) and the fasting urinary calcium/creatinine excretion ratio (+0.06 ± 0.004; P = 0.01) and significant decreases in the serum concentration of PTH (−32.9 ± 36.9 pg/mL; P< 0.001) and osteocalcin (−4.9 ± 2.4 ng/mL; P < 0.001). Vitamin D repletion was associated with a significant 4–5% annualized increase in bone mineral density at both the lumbar spine (P < 0.001) and the femoral neck (P = 0.03), indicating that resolution of vitamin D insufficiency in a population of patients with low bone mass results in a rapid rebound increase in bone mineral density.